Internalization of Character Education Values in the Khuruj Extracurricular Program - Rizal Mustamin; Arten Mobonggi; Hasyim Wantu (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2026)
This study aims to determine: (1) Stages of character education value formation in the extracurricular khuruj program at SMK Al Quran and Da'wah, Telaga Biru District; (2) Integration of character education values in the basis of da'wah for students at SMK Al Quran and Da'wah, Telaga Biru District. This study uses a qualitative method with a phenomenological approach carried out using observation, interview and documentation techniques. Techniques in data analysis, namely data reduction, data presentation, and conclusion/verification. The results of the study show that: (1) Stages of character value formation in the extracurricular khuruj program begin with value transformation, namely providing understanding to students with the aim of increasing motivation, so that the spirit of spirituality, commitment to self-improvement and actualization of the sunnah of the Prophet SAW grows. through advice lectures. Furthermore, value transactions include coaching or active involvement of educators with students such as role models, habituation and discipline coaching so that they become good behavior through an intense and consistent mentoring process. The final stage is transinternationalization, which forms the character values of religious, independent, with integrity and social students; (2) The khuruj activities implemented adopt the basis of da'wah which integrates religious, integrity, independence and social values. Religious values are manifested through the strength of strengthening faith through dhikr, perfecting the quality of prayer, as well as knowledge and dhikr activities which form disciplined worship and awareness of divinity. Integrity values are internalized through maintaining sincere intentions, istigfar and revitalizing the sunnah of the Prophet SAW, thus building inner honesty and noble morals. Independence is manifested through 1-day Itiqaf in the mosque so as not to depend on others. Social values are manifested through reverence and tabligh and silaturahmi activities which strengthen Islamic brotherhood